2014
DOI: 10.3727/096368913x663596
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Magnetic Resonance Imaging of Transplanted Hepatocytes in a Rat Model of Acute Liver Failure

Abstract: Hepatocyte transplantation is being evaluated as an alternative to liver transplantation. However, the fate of hepatocytes after transplantation is not well defined. The aims of the study were to improve hepatocyte labeling in vitro using superparamagnetic iron oxide nanoparticles (SPIOs) and to perform in vivo experiments on tracking labeled cells by magnetic resonance imaging (MRI). Human and rat hepatocytes were labeled in vitro for 16 h with clinically approved SPIOs (12.5 µg Fe/ml) and protamine sulfate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…MR imaging has proven to be an effective technique to monitor transplanted cells labeled with magnetically visible contrast agents in vivo . In agreement with previous findings , our data demonstrated that SPIO‐labeled BMSCs can be tracked by MR imaging within a short period (<12 days) after transplantation into rats with liver fibrosis.…”
Section: Discussionsupporting
confidence: 91%
“…MR imaging has proven to be an effective technique to monitor transplanted cells labeled with magnetically visible contrast agents in vivo . In agreement with previous findings , our data demonstrated that SPIO‐labeled BMSCs can be tracked by MR imaging within a short period (<12 days) after transplantation into rats with liver fibrosis.…”
Section: Discussionsupporting
confidence: 91%
“…Over the last two decades there has been an increase in the use of magnetic particles and magnetic microspheres including iron oxide nanoparticles (IONPs) and superparamagnetic iron oxide nanoparticles (SPIONs) for bio-medical applications such as imaging, diagnostics, therapies and theranostics, but their suitability for these applications ultimately depends on their biodistribution and toxicity profiles [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20]. The two main administration routes for IONPs into the body are intravenous (IV) injection and intraperitoneal (IP) injection.…”
Section: Introductionmentioning
confidence: 99%
“…We are aware that our current findings are limited only to the course of TAA-induced ALF, however recently hepatocyte Tx was successfully used in the treatment of another chemical models of ALF (e.g. D-galactosamine-induced ALF) (Puppi et al 2014) and therefore we believe that our present results should be reproducible in other models of ALF and such studies are necessary to be performed in future.…”
Section: Discussionmentioning
confidence: 71%
“…2 x 10 6 ) was transplanted. In accordance with these findings in liver-based metabolic diseases, also other investigators have recently started to use similar amount of cells for the treatment of ALF (Amano et al 2011, Fukumitsu et al 2011, Jitraruch et al 2014, Loukopoulos et al 2014, Puppi et al 2014. Untreated rats (without hepatocyte Tx) received 600 µl of physiological solution by the same route.…”
Section: Ethical Approval Animals Chemicals and Isolation And Tranmentioning
confidence: 76%